Hypoxic breathing produces more intense hypoxemia in elderly women than in elderly men - Zhao, Jinfeng; Ding, Yanfeng; Kline, Geoffrey P.; Zhou, Zhengyang; Mallet, Robert T.; Shi, Xiangrong (Frontiers in Physiology, 2022)
Background Brief hypoxic exposures are increasingly applied as an intervention for aging-related conditions. To optimize the therapeutic impact of hypoxia, knowledge of the sex-related differences in physiological responses to hypoxia is essential. This study compared hypoxia-induced hypoxemic responses in elderly men and women. Methods Seven elderly men (70.3 ± 2.3 years old) and nine women (69.4 ± 1.8 years old) breathed 10% O2 for 5 min while arterial (SaO2; transcutaneous photoplethysmography) and cerebral tissue O2 saturation (ScO2; near-infrared spectroscopy), ventilatory frequency, tidal volume and minute-ventilation, and partial pressures of end-tidal O2 (PETO2) and CO2 (Mass Spectrometer) were continuously monitored. Cerebral tissue oxygen extraction fraction (OEF) equaled (SaO2–ScO2)/SaO2. Results During 5 min hypoxia SaO2 fell from 97.0 ± 0.3% to 80.6 ± 1.7% in the men and from 96.3 ± 0.5% to 72.6 ± 1.3% in the women. The slope SaO2/min was steeper in the women than the men (-4.71 ± 0.32 vs -3.24 ± 0.29%/min; P=0.005). Although SaO2 fell twice as sharply per unit decrease in PETO2 in the women than the men (1.13 ± 0.11 vs 0.54 ± 0.06%/mmHg; P=0.003), minute-ventilation per unit hypoxemia increased less appreciably in the women (-0.092 ± 0.014 vs -0.160 ± 0.021 L/min/%; P=0.023). OEF fell with hypoxia duration in the women, but remained constant in the men. Conclusion During 5 min hypoxic breathing, elderly women experience more intense hypoxemia, augmented O2 dissociation from hemoglobin, and reduced chemoreflex sensitivity vs their male counterparts, which may lower OEF stability in women during hypoxia. These sex-related differences merit attention when implementing brief hypoxic exposures for optimal therapeutic purposes.